Zircon micro-inclusions as an obstacle for in situ garnet U–Pb geochronology: an example from the As Sifah eclogite locality, Oman - J. B. Walters; J. B. Walters; J. B. Walters; J. M. Garber; A. Beranoaguirre; A. Beranoaguirre; L. J. Millonig; L. J. Millonig; A. Gerdes; A. Gerdes; T. Grützner; T. Grützner; et al. (Geochronology)
Garnet is commonly used to calculate pressure (P)–temperature (T) histories of metamorphic rocks, as well as to monitor changes in bulk-rock composition (X) and deformation (d). In situ U–Pb geochronology by laser ablation–inductively coupled mass spectrometry (LA-ICPMS) is a rapid and relatively high spatial resolution technique, which can be used to constrain the timing of the metamorphic P–T–X–d histories preserved in garnet. However, the low U contents (low µg g−1 to ng g−1 levels) of most common metamorphic garnet crystals present unique analytical challenges, including potential contamination of the U–Pb system by high-U inclusions, such as zircon, rutile, monazite, and apatite. Here we use laser ablation split-stream (LASS) ICPMS (LASS-ICPMS) analysis to simultaneously measure the U, Th, and Pb isotopes and trace-element contents of eclogite-facies garnet from metamafic rocks at As Sifah, Oman. We observe abundant zircon micro-inclusions (<2 µm) in all five dated samples. Strong linear correlations in U vs. Zr contents in the analysed laser ablation spots plot along garnet–zircon mixing lines, the slopes of which can only be explained by zircon contamination. Despite clear zircon contamination in the trace-element data, the time-resolved laser ablation U and Pb signals show some irregularities but lack sharp diagnostic spikes typically indicative of inclusions. Instead, zircon micro-inclusions are sufficiently small, abundant, and dispersed over the scale of the laser spot site (193 µm diameter) such that their contributions to the U, Th, and Pb signals are diluted to produce irregular time-resolved signals that have previously not been identified as inclusions.